Euthanasia In Indonesia: Laws, Human Rights, And Medical Perspectives - Ohoiwutun, Y. A. Triana; Taniady, Vicko; Lutfian, Lutfian; Rachim, Kania Venisa; Putri, Natasya Aulia (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2024)
Euthanasia remains a contentious issue in Indonesia, where it is currently prohibited by law, creating significant challenges in balancing human rights, legal standards, and medical ethics. This research explores the legal framework, human rights considerations, and medical perspectives surrounding euthanasia in Indonesia, with a comparative analysis of practices in the Netherlands. Employing a normative legal research methodology, it utilizes legislative analysis, case studies, and comparative approaches to examine the regulatory gaps and societal implications of euthanasia in Indonesia. The findings reveal that while active euthanasia is explicitly criminalized under Indonesian law, passive euthanasia occurs discreetly within society, reflecting a legal and ethical gray area. Comparatively, the Netherlands' regulated approach provides valuable insights into balancing patient autonomy and societal ethics. This study concludes that Indonesia could benefit from legalizing passive euthanasia under stringent conditions, aligned with human rights principles and cultural values. This legalization would require robust regulatory frameworks, including judicial oversight and ethical guidelines, to ensure accountability and safeguard vulnerable groups. The findings underscore the urgency of harmonizing legal, human rights, and medical perspectives to address this complex issue while respecting Indonesia's unique socio-cultural context.